Same-Session Hybrid Embolization and Microsurgery Versus Endovascular-Only Treatment for Cerebral Arteriovenous Malformations: A Retrospective Single-Center Comparative Cohort Study - Hasan Bilen Onan; Bişar Akbaş; Ferhat Can Pişkin; Kadir Oktay; Kerem Mazhar Özsoy; Duygu Özgül Özesen; Erol Akgül (Journal of Clinical Medicine, 2026)
Background/Objectives: Same-session hybrid treatment joins embolization to immediate microsurgical resection under one anesthetic, closing the interval of partial devascularization that follows staged embolization. Comparative data are scarce. We set out to compare angiographic, functional and safety outcomes after hybrid and after endovascular-only treatment and to judge how far any difference reflects case selection and calendar period rather than the strategies themselves. Methods: We reviewed 43 consecutive patients treated for cerebral arteriovenous malformation at one center between May 2012 and December 2024. Nineteen received same-session hybrid treatment and 24 embolization without same-session surgery. The primary endpoint was complete obliteration on six-month angiography. Differences are reported with 95% confidence intervals, and odds ratios were estimated using Firth penalized regression, since both principal comparisons showed complete separation. Results: Hybrid patients were younger (median 31.0 versus 42.5 years; p = 0.040), with similar sex distribution and Spetzler–Martin grade. Complete obliteration was reached in all 19 hybrid patients (100%) and in 14 of 24 endovascular-only patients (58.3%), representing a difference of 41.7 percentage points (95% CI 17.6–61.2). All four deaths occurred in the hybrid group (21.1% versus 0%; p = 0.031). Complications (15.8% versus 12.5%) and favorable outcome (mRS 0–2, 68.4% versus 75.0%) did not differ. The strategies also belonged to different periods. Eight of 19 hybrid but 21 of 24 endovascular patients were treated before 2019 (p = 0.003), as were three of the four deaths. Conclusions: The hybrid treatment obliterated every malformation but accounted for every death, with no difference in functional outcome. Because the groups served different clinical purposes in different eras, these observations are hypothesis-generating rather than grounds for changing practice.